DESKRIPSI TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN IMUNISASI PENTAVALEN PADA BAYI DI BIDAN PRAKTEK MANDIRI (BPM) INDARWATI MRANGGEN JATINOM KLATEN - Nuryanti .; Kemaludin .; Ika Winarningrum (STIKES DUTAGAMA KLATEN, 2015)
Background: Coverage DPT1 and HB1 in Klaten regencyin 2013 some 17 947 (101.6%), coverage of DPT3 + HB3 there are 18 264 (103.4%). DO Drop out or full immunizationin Klaten regencyin 2013 amounted to -2.6%. Research Objectives: to know the phenomenon of the description of the level of knowledge of mothers about infant pentavalent immunization. Research Methods: This study is a qualitative descriptive with cross sectional approach. The population in this study are all mothers with infants aged 2-4 month sin by ± 38 informants. Sampling Quota sampling with a number of 14 informants. Research Results: The knowledge of mothers about infant pentavalent immunization. in-depth interviews of high category (25,0%), moderate (25,0%), low (50,0%), knowledge of mothers about the benefits of immunization pentavalent low categorized (83.3%), low categorized pentavalent immunization schedule (33.3%), concomitant effects after being given a pentavalent immunization categorized high (83.3%). Conclusion: Description of the level of knowledge of mothers about infant immunization with pentavalent low category (83.3%).